Sistem Pendukung Keputusan Penerimaan Bantuan SosialProgram Keluarga Harapan Menggunakan Metode Multy Attribute Utility Theory - Salsabila Delaisya Permana; Dwiny Meidelfi; Rahmat Hidayat (Politeknik Caltex Riau, 2022)
There are several Social Assistance (BANSOS) distributed by the Ministry of Social Affairs to each village, one of which is the Family Hope Program (PKH) social assistance which is a program of providing conditional social assistance to poor families (KM) designated as PKH recipient households. So far, for checkingthe data of proposing aid, the social service staff still uses the manual method so it takes a long time, but in this study the author created a system that will later assist the process of managing data for PKH beneficiaries so that results will be faster and more accurate. which makes the provision of PKH assistance more targeted.The methodthat will be used in the decision support system for receiving social assistance this time is the Multi Attribute Utility Theory method, and the data collection technique is literature study and observation.The results to be obtained are in the form of recommendations for decision making regarding the determination of PKH assistance.